PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG DALAM HUKUM PIDANA - Sihombing, Finiel Handani Tumalona; Chandra, Tofik Yanuar; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Human Trafficking is the act of recruiting, transporting, harboring, sending, transferring, or receiving a person by means of threats of violence, use of violence, kidnapping, confinement, forgery, fraud, abuse of power or vulnerable position, debt bondage or giving payments or benefits, so as to obtain the consent of a person who holds control over another person, whether carried out within the country or between countries. The formulation of the problem in this study is How is the Legal Protection for victims of the Crime of Human Trafficking and How is the Criminalization of the Crime of Human Trafficking in Criminal Law. The theory used in this study is the theory of Legal Protection and the theory of Criminalization. The method used in this research is a normative juridical research type, namely library legal research or secondary data with primary, secondary, and tertiary legal material sources. The research approaches used are the statutory approach, case approach, analytical approach, and conceptual approach. The legal material collection technique is carried out by identifying and inventorying positive legal regulations, book literature, journals, and other legal material sources. The legal material analysis technique is carried out by legal interpretation (interpretation), grammatical interpretation, and systematic interpretation.The research findings show that legal protection for victims of human trafficking, based on Law Number 21 of 2007, regulates the protection of victims of human trafficking as an important aspect of law enforcement. Furthermore, Article 48 provides for restitution for victims, but its implementation still faces various obstacles. Specifically, the victim's right to restitution lacks procedures that simplify the restitution application process and the provision of substitute fines for convicts. Many perpetrators' sentences are still not appropriate in practice, with court sentences often falling far below the maximum penalty. This creates a gap between legal norms and their implementation, and leads to dissatisfaction and a sense of injustice for victims. Criminal penalties tend to be minimal, and some are below the minimum.